Sociological Analysis of Pekanbaru-Kampar Agglomeration's Response to Infrastructure Development: A Structural and Functional Analysis - Hidir, Achmad; Yusuf, Yusmar; Syafrizal, Syafrizal (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
This study aims to examine and comprehend the structural and functional responses of the community in Tambang District, Kampar Regency, to the construction of the Trans-Sumatra Toll Road interchange. This large-scale infrastructure development has triggered the inevitable phenomenon of urban agglomeration, changing the physical and socio-economic landscape of the region. This study uses a descriptive-analytical qualitative approach with a single case study design. Data was collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model. Tambang Subdistrict evolved into a strategic hub characterized by substantial alterations in spatial planning, land utilization, and the reconfiguration of ownership. Functionally, mobility drastically improved, but the economic impacts on Micro, Small, and Medium Enterprises (MSMEs) were profoundly varying. The findings reveal an economic dichotomy: MSMEs, like Dapur Aru, experienced increased turnover due to expanded accessibility, while traditional MSMEs, like Lopek Bugi, faced a decline due to disruption in traditional access patterns. These results support the Growth Pole Theory but offer a nuanced contribution by showing how the developmental effects are uneven at the micro-community level, aligning with Structural Functionalism. The conclusion underscores the urgency of more targeted and adaptive MSME mitigation and empowerment policies to ensure local socio-economic sustainability amid development.